Prediction of microstructure composition in steel plate heated using high power Yb:YAG laser radiation - Kubiak Marcin (MATEC Web of Conferences, 2019)
This work concerns numerical modelling and computer simulations of temperature field and phase transformations during Yb:YAG laser heating of sheets made of S355 steel. The distribution of laser power emitted by Trumpf laser head D70 is used in the analysis. The heat source is modelled on the basis of interpolation algorithms using geostatistical kriging method. Coupled heat transfer and fluid flow in the fusion zone are described respectively by transient heat transfer equation with convective term and Navier-Stokes equation. The kinetics of phase transformations and volumetric fractions of arising phases are obtained on the basis of Johnson-Mehl-Avrami (JMA) and Koistinen-Marburger (KM) models. Continuous Heating Transformation (CHT) diagram is used for heating process and Continuous Cooling Transformation (CCT) diagram is used for heated steel with the decomposition of final volume fractions of phases transformed form austenite dependant on cooling rates.